The Application of a Decision-making Approach based on Fuzzy ANP and TOPSIS for Selecting a Strategic Supplier - Govindaraju, Rajesri; Akbar, Muhammad I.; Gondodiwiryo, Leksananto; Simatupang, Tota (Journal of Engineering and Technological Sciences, 2015)
Supplier selection becomes very important when used in the context of strategic partnerships because of the long-term orientation of the relationship. This paper describes the application of a decision-making approach for selecting a strategic partner (supplier). The approach starts with defining a set of criteria that fits the companyâs condition. In the next steps, a combination of fuzzy-ANP and TOPSIS methods is used to determine the weight for each criterion and rank all the alternatives. The application of the approach in an Indonesian manufacturing company showed that the three factors that got the highest weight were âgeographical locationâ, âcurrent operating performanceâ, and âreliabilityâ. Geographical location got the highest weight because it affects many other factors such as reaction to changes in demand, after-sales service, and delivery lead-time.Â  Application of the approach helps decision-makers to gain effectiveness and efficiency in the decision-making process because it facilitates them to express their groupâs collective preferencesÂ  while also providing opportunities for members to express their individual preferences. Future research can be directed at combining qualitative and quantitative criteria to develop the best criteria and methods for the selection of the best suppliers based on fuzzy ANP and TOPSIS.